SINERGISME DAN ANTAGONISME BEBERAPA JENIS ISOLAT BAKTERI YANG DIKONSURSIUMKAN - Muhammad Rustam Rifai; Hening Widowati; Agus Sutanto (BIOLOVA, 2020)
Abstract: The microorganism consortium is a mixture of microbial populations in the form of communities that have cooperative, commensal, and mutualistic relationships. Naturally bacteria are able to communicate with each other. Synergism is two species that live together and carry out activities that do not interfere with each other, but their activities are in conflict with a mutually beneficial sequence, so the living relationship between species is called synergism. Antagonism expresses an ial relationship. One species produces something that poisons the other species, so the growth of the latter species is very difficult. to support the interaction of several types of microbes that are mutually beneficial / synergistic. To serve antibiosis / antagonism of several types of microbes.